Sistem Pendukung Keputusan Untuk Menentukan Tarif Maksimum Kamar Hotel Garuda Plaza Medan Dengan Metode Fuzzy Tsukamoto - Wahyu Prismawan; Efori Bu'ulolo; A.M. Hatuaon Sihite (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Medan City is a Metropolitan city and also many tourist objects that are currently popular among Indonesians and foreigners. In the hotel industry, the most important thing in determining the hotel rental price is because it only estimates the price of the hotel being rented based on the type of hotel and the facilities provided. Where the problems that occur to consumers do not know the price of the hotel for rent based on the type of hotel room, so that the customer has difficulty in determining the choice of room to use. Based on this problem, Fuzzy Tsukamoto was chosen because it has monotonous reasoning in each of its rules, where each consequent to the rule in the form of IF-THEN must be represented by a fuzzy set with a monotonous membership function. Fuzzy logic is used to solve problems linguistically or variables that contain uncertainty rather than through numbers. The Tsukamoto method has 3 stages, namely; fuzzification, fuzzy inference system, and defuzzification. Fuzzification functions to change crisp values ??to fuzzy values. Fuzzy inference system is drawing conclusions based on fuzzy rules or rules. Defuzzification is the process of converting fuzzy output into crisp values ??using the weighted average concept. In this study the rules will be searched automatically by the system based on the data that has been entered. The data that has been entered will be added with "events" to distinguish holidays, significant price changes, and the like. The results of this study obtained an error using MAPE of 28.41% for the test data with the Studio room type and 27.85% for the test data with the Premiere room type.